Financial Literacy, Financial Technology, and Access to Finance as Determinants of MSME Sustainability: Evidence from Culinary MSME in Palangka Raya - Johannes Ficher Sinaga; Rita Sarlawa; Evinalia Yeba; Dhina Sri Widyaningsih (FEBI IAIN Langsa, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play a vital role in economic growth; however, their sustainability remains constrained by low financial literacy, limited utilization of financial technology (fintech), and restricted access to financing. Previous studies have reported inconsistent findings regarding the effects of these factors on MSME sustainability, indicating the need for further empirical evidence, particularly in the culinary sector. This study aims to examine the effects of financial literacy, financial technology, and access to finance on the sustainability of culinary MSMEs in Palangka Raya City. A quantitative survey approach was employed. A total of 98 respondents were selected using purposive sampling, while the sample size was determined using the Slovin formula. Data were analyzed using multiple linear regression with SPSS version 27. The results indicate that financial literacy has a positive and significant effect on MSME sustainability (β = 0.269; p < 0.001), financial technology has a positive but insignificant effect (β = 0.049; p = 0.567), and access to finance has a positive and significant effect (β = 0.243; p = 0.002). Simultaneously, the three independent variables significantly influence MSME sustainability (F = 15.665; p < 0.001), with an adjusted coefficient of determination of 33.3%. These findings suggest that improving financial literacy and expanding access to finance are essential for enhancing MSME sustainability, whereas the utilization of financial technology should be optimized to generate greater business value. This research provides a scientific contribution by strengthening the empirical evidence regarding the integration of financial literacy, financial technology, and access to finance in explaining MSME sustainability through the perspectives of the Resource-Based View, Behavioral Life Cycle Theory, and Technology Acceptance Model.